The influence of extraction methods on rutin yield of cassava leaves (Manihot esculenta Crantz) - Agus Chahyadi; Elfahmi (Elsevier, 2020)
Rutin, a well-known bioflavonoid, was found abundantly in cassava leaves. In the present study, extraction techniques including maceration, boiling, reflux, ultrasound-assisted extraction (UAE), and microwave-assisted extraction (MAE) were optimised to increase the yield of rutin. Extraction parameters such as solvents, solid-liquid ratio, temperature, and time were optimised to give better extraction yields for each method. HPLC analysis showed a high content of rutin which is up to 2.4% per dry weight of cassava leaves. The extraction yields under optimised condition were found to be 16.00 ± 0.21, 20.38 ± 0.66, 22.33 ± 2.3, 24.49 ± 0.41, and 23.37 ± 1.00 g rutin per kg dry weight for maceration, boiling, reflux, UAE and MAE methods, respectively. Specifically, UAE reduced the extraction time to 90 min, using only 40-60% of aqueous ethanol. Meanwhile, MAE completed the extraction under 5 min and no significant differences in output was observed between the use of water and aqueous ethanol. Accordingly, with the extraction efficiency of up to 99 and 94%, respectively, both processes provided better results. The subsequent green purification using chilling method produced a typical cassava bioflavonoid containing 82% of rutin and 17% of nicotiflorin. This study informs a new abundant source of rutin and provides the optimum condition of extraction methods for high yield of rutin from cassava leaves.